2019
DOI: 10.21511/ppm.17(2).2019.28
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of corporate social responsibility of Ukrainian companies: clustering and improvement strategies for responsible activities

Abstract: The variability of companies stakeholders’ engagement forms, communication channels, approaches to disclosure of companies’ corporate social responsibility (CSR) and strategies for CSR achievement cause the formation of benchmarks – patterns of responsible behavior of these companies. Determination of companies’ CSR patterns plays is a ground of (plays a role or is a ground of) improving their strategies for responsible activities. These patterns were highlighted on the basis of comprehensive three-component i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Oleh karena itu, para manajer perlu memahami peran CSR dalam meningkatkan reputasi dan daya saing perusahaan. Selain itu, mereka juga harus mengembangkan strategi pelibatan pemangku kepentingan yang komprehensif untuk meningkatkan dampak program CSR dan menyelaraskannya dengan harapan para pemangku kepentingan yang berbeda (Sukhonos et al, 2019). Kesimpulannya, adopsi pandangan CSR yang lebih strategis dan holistik di Indonesia memberikan peluang yang sangat baik bagi perusahaan untuk menciptakan nilai bersama sekaligus berkontribusi secara positif kepada masyarakat.…”
Section: Pengaruhunclassified
See 1 more Smart Citation
“…Oleh karena itu, para manajer perlu memahami peran CSR dalam meningkatkan reputasi dan daya saing perusahaan. Selain itu, mereka juga harus mengembangkan strategi pelibatan pemangku kepentingan yang komprehensif untuk meningkatkan dampak program CSR dan menyelaraskannya dengan harapan para pemangku kepentingan yang berbeda (Sukhonos et al, 2019). Kesimpulannya, adopsi pandangan CSR yang lebih strategis dan holistik di Indonesia memberikan peluang yang sangat baik bagi perusahaan untuk menciptakan nilai bersama sekaligus berkontribusi secara positif kepada masyarakat.…”
Section: Pengaruhunclassified
“…Mengingat semakin meningkatnya kesadaran dan pentingnya CSR di Indonesia, penting bagi perusahaan untuk tidak hanya mengimplementasikan inisiatif, tetapi juga memahami bagaimana berbagai faktor seperti norma budaya, sosial, dan ekonomi berdampak pada efektivitas inisiatif ini. Singkatnya, agar perusahaan dapat memaksimalkan manfaat dari inisiatif CSR di Indonesia, rencana pelibatan pemangku kepentingan yang komprehensif dan strategis harus dikembangkan (Sukhonos et al, 2019). Selain itu, perusahaan harus fokus untuk mengidentifikasi dan menangani harapan dan kekhawatiran pemangku kepentingan untuk memastikan keberlanjutan inisiatif CSR mereka.…”
Section: Pengaruhunclassified
“…However, the level of SDGs progress in Ukraine compared to the 50 leading countries in the world is low -46th out of 149 countries in the 2016 Global SDG Indicators Database (2016). Sukhonos et al (2019) showed that corporate social responsibility activity in Ukraine is relatively low because of the low perception of sustainability ideology and reporting. Plastun et al (2021) provide some preliminary explanation of SDGs 2 and 12 disclosure achievements in Ukraine agriculture companies and found that problems in their achieving are similar for these countries.…”
Section: According To the Msci (Morgan Stanley Capitalmentioning
confidence: 99%
“…Many contributions in the literature corroborate the need to include environmental aspects in the definition of CSR; otherwise, the relationship between responsibility towards society and towards the environment is not immediate (Schönherr et al , 2017). A self-centred vision represents, in fact, only the first step identified in the literature to move towards a solution co-created with other actors, which is characterised by reactive rather than proactive behaviour (D’Antonio and Sim, 2017; Keijzers, 2012; Porter and Kramer, 2011; Sukhonos et al , 2019). Similarly, Caldera et al (2018) propose concrete actions depending on the stage the firm is at, which, according to Hart (2013) involves moving from the passive phase of prevention of environmental damage to assuming product stewardship and pursuing proactive sustainable development.…”
Section: Current Difficulties Of Multinational Enterprises In Pursuin...mentioning
confidence: 99%